Scleroderma and scleroderma-like syndromes - Romanowska-Próchnicka, Katarzyna; Dziewit, Martyna; Lesiak, Aleksandra; Reich, Adam; Olesińska, Marzena (Frontiers in Immunology, 2024)
Systemic sclerosis is a systemic connective tissue disease whose main pathophysiological mechanism is a progressive fibrosis of the skin leading to thickening and induration. Internal organs and blood vessels may also be involved. However, systemic sclerosis is not the only disease causing cutaneous sclerosis. There is a group of diseases that mimic scleroderma in their clinical presentation - these are scleroderma-like syndromes. A distinction can be made between syndromes of inflammatory/autoimmune, genetic, metabolic, toxic, drug-induced, occupational, paraneoplastic and syndromes caused by deposition disorders. In the following paper, we have reviewed the literature on scleroderma-like syndromes. We have outlined the factors predisposing to the development of each disease, its pathogenesis, clinical presentation, diagnostic and treatment process and the differences between each syndrome and systemic sclerosis.